Colorectal carcinoma: evaluation of systemic values of interleukin-1 and interleukin-33 in patients with and without thrombocytosis - Jocić, Miodrag; Gajović, Nevena; Jurišević, Milena; Jovanović, Marina; Zdravković, Nataša; Arsenijević, Nebojša; Vuković Dejanović, Vesna; Marić, Veljko; Milev, Boško; Jovanović, Milan (Vojnosanitetski pregled, 2021)
Background/Aim. Reactive thrombocytosis, as a paraneoplastic syndrome, is often observed in cancer patients. A variety of tumor-related humoral factors and cytokines contribute to tumor-stimulated thrombopoiesis. However, the exact role of these cytokines in the pathogenesis of thrombocytosis remains unclear. The aim of this study was to analyze systemic values of cytokines and clinical-pathological characteristics in colorectal carcinoma (CRC) patients with and without thrombocytosis. Methods. Fifty nine CRC patients were involved in this study and divided into two groups according to the number of platelets. We recorded and analyzed the data about: age, gender, size of the cancer, localization, metastasis, vascular or lymph vessel invasion, nuclear grade, histological differentiation rate, tumor, nodus, metastasis (TNM) stage and concentration of cytokines [interleukin (IL)-1, IL-33, IL-12, IL-17 and interferon (IFN)-γ] in both groups. Results. CRC patients with thrombocytosis had significantly higher nuclear grade of the cancer (p = 0.002); higher percentage of detectable metastatic lesions in the liver (p = 0.002), lung (p = 0.001), peritoneal carcinomatosis (p = 0.001), detectable invasion of blood (p = 0.012) and lymph vessels (p = 0.010). Concentrations of tumor markers [alpha-fetoprotein (AFP), carcinoembryonic antigen (CEA) and cancer antigen 19-9 (CA19-9)] and serum values of IL-1 and IL-33 were significantly higher in CRC patients with thrombocytosis. IL-1/IL-12 (p = 0.016), IL-1/IFN-γ (p = 0.007), IL-1/IL-17 (p = 0.006), IL-33/IL-12 (p = 0.001), IL-33/IFN-γ (p = 0.001), IL-33/IL-17 (p = 0.002), and IL-33/IL-1 (p = 0.006) ratios were significantly higher in CRC patients with thrombocytosis in comparison to CRC patients without thrombocytosis. Analysis of Receiver Operating Characteristic (ROC) curves showed that values of IL-1 [area under curve (AUC) = 0.718; 95% confidence interval (CI): 0.567–0.868; sensitivity 69.2%, specificity 62.9%] and IL-33 (AUC = 0.763; 95% CI: 0.614–0.911; sensitivity 84.6%, specificity 65.7%)], could be serve as possible markers for paraneoplastic thrombocytosis in CRC patients. Conclusion. IL-1 and IL-33 significantly correlated to high thrombocyte number in patients with more aggressive CRC.
Keywords: colorectal neoplasms; thrombocytosis; cytokines; interleukins.